THE POTENTIAL OF NGOKILO LEAVES EXTRACT (STACHYTARPHETA MUTABILIS. VAHL) AS A LOWERING OF BLOOD GLUCOSE LEVELS OF WHITE MICE (RATTUS NORVEGICUS) - Mimatun Nasihah (Universitas Medan Area, 2021)
Diabetes is a disease, in which the body cannot produce enough insulin so that there is excess sugar in the blood which becomes toxic to the body. Ngokilo plants are believed to be able to lower blood sugar levels because of the antioxidants and polyphenols contained therein.The objective of this study was to determine the potential of the ethanol extract of Ngokilo leaves (Stachytarpheta mutabilis, Vahl) as a lowering blood glucose levels in white mice(Rattus norvegicus). The tests were carried out by an experimental method using Swiss Webster male mice (Rattus norvegicus) aged 2-3 months with a body west of 30-40 grams as test animals. This study used four dosage ratios of ngokilo leaf extract, namely 1: 20: 40: 60 and control used aquadest. The results showed that the ethanol extract of Ngokilo leaves had an F value of 27.033> F Table 2.60. It indicates that the independent variable (the difference in the concentration of ethanol extract of Ngokilo leaves) was proven to have a significant effect on the dependent variable (blood sugar levels).